The use of rooibos (Aspalathus linearis) and honeybush (Cyclopia spp.) as wood alternative in red winemaking - De Wet, Alet (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.